A floodplain with artificially reversed flood pulse is important for migratory rare bird species - Robinson, Vivian [UNESP]; Pizo, Marco A. [UNESP] (Springer Nature, 2017)
Wetlands are increasingly scarce and the construction of water-flow regulation structures is predicted to increase in the coming years. The correct management of these impacted areas may play an important role in the conservation of wetland bird species. In a floodplain whose natural flood pulse was reversed in relation to local rainfall seasonality by the construction of a dam (the Tanquã floodplain), we investigated how the composition and abundance of the waterbird community varied with the water depth to understand how artificially maintained flooded areas could sustain different bird functional groups, preventing future biodiversity losses. We recorded 72 waterbird species, 17 reproducing in the area. Seventeen species are short-distance migrants in Brazil, while eight are long-distance migrants. As overall bird abundances are negatively correlated with the water depth, any further modification in the flood-pulse may cause the area to lose its ability to support its biodiversity. Future dam construction projects should take actions to transform or maintain their areas of influence as important habitats for the threatened waterbird community, thus contributing to their conservation.
Keywords: Bird functional groups; Dam impacts; Waterbirds; Wetland management; Wetlands